2004
DOI: 10.1063/1.1736675
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of vortical structures around a wall-mounted cubic obstacle in channel flow

Abstract: Vortical structures around a wall-mounted cubic obstacle in channel flow are studied using numerical simulation. Flows of low-to-moderate Reynolds numbers up to Reϭ3500 are considered. The objective of this work is to elucidate characteristics of coherent vortical structures produced by the presence of the wall-mounted cubic obstacle, including horseshoe vortex systems upstream of the obstacle, lateral vortices in the vicinity of the two lateral faces of the cube, and hairpin vortices in the near-wake region. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
43
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 26 publications
8
43
1
Order By: Relevance
“…The wake region is typified by the presence of a recirculation flow consisting of vortex flow patterns. Similar vortices have also been observed for particle flux around wallmounted cubic obstacles in flow channels [52][53][54][55][56], around geographical mountains or hills [57], around islands in shallow water [58,59], and airflows around buildings [60,61]. In this case study we examine the effect of a particle flux with varying Re on the velocity field in the vicinity of a square obstacle of side l placed at the center of a flow channel.…”
Section: Flow Around An Obstaclesupporting
confidence: 55%
“…The wake region is typified by the presence of a recirculation flow consisting of vortex flow patterns. Similar vortices have also been observed for particle flux around wallmounted cubic obstacles in flow channels [52][53][54][55][56], around geographical mountains or hills [57], around islands in shallow water [58,59], and airflows around buildings [60,61]. In this case study we examine the effect of a particle flux with varying Re on the velocity field in the vicinity of a square obstacle of side l placed at the center of a flow channel.…”
Section: Flow Around An Obstaclesupporting
confidence: 55%
“…They pointed out that when the flow passes a square cylinder, the large-scale eddies depend strongly upon the small-scale perturbations, and thus it is difficult to determine how much resolution is adequate in calculating the pressure and the force in the structure. Hwang et al [7] used the direct numerical simulation (DNS) to study the vortical structures around a wallmounted cubic obstacle in laminar flow in a channel. The moderate Reynolds numbers vary until 3500.…”
Section: Introductionmentioning
confidence: 99%
“…Hwang et al [2] studied numerically the vortical structures around a wall mounted cubic obstacle in a laminar channel flow from low to moderate Reynolds numbers up to 3500. They concluded that flow becomes turbulent in the near wake region at low Reynolds numbers itself.…”
Section: Introductionmentioning
confidence: 99%